Impact of Concomitant Thrombotic Thrombocytopenic Purpura on COVID-19 Mortality and Morbidity: A Nationwide Inpatient Sample Analysis - Ali Jaan MD; Zouina Sarfraz MBBS; Farhan Khalid MD; Junaid Anwar MD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Utilizing the comprehensive Nationwide Inpatient Sample (NIS) database, we examined the impact of thrombotic thrombocytopenic purpura (TTP) on the outcomes of patients with coronavirus disease-19 (COVID-19), emphasizing the potential role of the ADAMTS13 enzyme in disease pathogenesis and evolution. We analyzed extensive data from the NIS database using STATA v.14.2 and accounted for potential confounders using multivariate regression analysis to uphold the validity and reliability of the study. Among 1 050 045 adult patients hospitalized with COVID-19, only 300 (0.03%) developed TTP. These patients were younger (mean age 57.47 vs 64.74, P < .01) and exhibited a higher prevalence of preexisting conditions, such as congestive heart failure (13.33% vs 16.82%, P value not provided) and end-stage renal disease (3.33% vs 3.69%, P value not provided). On multivariate regression analysis, COVID-19 patients with concomitant TTP demonstrated a significant increase in mortality (adjusted odds ratio [AOR] 3.99, P < .01), venous thromboembolism (AOR 3.33, P < .01), acute kidney injury (AOR 7.36, P < .01), gastrointestinal bleeding (AOR 10.75, P < .01), intensive care unit admission (AOR 14.42, P < .01), length of hospital stay (17.42 days, P < .01), and total hospitalization charges ($298 476, P < .01). Thrombotic thrombocytopenic purpura in COVID-19 patients elevates the risk of mortality and complications, likely driven by the thrombotic nature of TTP. Our data underline the potential significance of ADAMTS13 in COVID-19 and TTP pathophysiology, suggesting its possible role as a therapeutic target.